INTER-RACIAL HETEROSIS IN MAIZE HYBRIDS (Biological Sciences - PJSIR, 2001)
Seventy-seven single cross maize hybrids alongwith four checks were evaluated at the NWFP Agricultural University Peshawar Research Farm during Khanf 1997 to determine the magnitude of heterosis and combining ability in elite mbred Imes and to identify hybnds for commerci~l production. Hybrids CMIAO x SY8-2 and K305 x CML66 produced the highest gram YIeldsof 3995 and 3837 kg ha showing 19% and 14% heterosis, respectively, over the best check Cargill 707. The top YI~ldmghybrids had desirable plant heights (ranging 132-166 ern) and were observed in maturity (97-100 days) at par WIth the local check vaneties. Inbred hnes CML-40 and CML-66 were identified as good general combiners for gram Yieldwhile NC-298 and SW 49-2 showed good specific combining ability for the same trait.